Prevalence of Overweight and Obesity among Adolescents: A School-Based Preliminary Cross-Sectional Study - Mathew, Shycil; D'Souza, Jenifer; Saldanha, Prakash (Journal of Health and Allied Sciences NU, 2022)
Introduction Globally, the magnitude of overweight and obesity is alarmingly high. In recent years, there are increased opportunities for adolescents to become overweight due to their sedentary lifestyles. Obesity is a chronic, noncommunicable, and lifestyle diseases resulting from energy imbalance. On evidence, overweight and obesity are still preventable as primordial prevention. Thus, knowing the prevalence will help us to plan prevention strategies.Objectives The objective of the study was to identify the prevalence of overweight and obesity among adolescents in selected urban high schools at Mangaluru, Dakshina Kannada, India.Materials and Methods A quantitative descriptive cross-sectional study was performed in adolescents with the age group of 13 to 15 years. Data was collected by using a body mass index screening tool through Google Forms. A total of 1100 adolescents participated in the study.Results Almost 82.2% of the total adolescents were in the age group of 13 years with a mean age of 13.95 ± 1.02 standard deviation. Most 70% of them were females and 98.1% of adolescents place of stay was at home. Magnitude of overweight and obesity among urban adolescents in this study was 237(21.6%). A significant positive association was found between body mass index with selected demographic variables such as age, family history of overweight and obesity, and screen time more than 2 hours per day among adolescents with a p less than 0.05 level of significance.Conclusion This study revealed that current magnitude of overweight and obesity among adolescents is growing high. Health promotion activities need to be planned and there is a need to identify the challenges to implement such activities. Irrespective of all the barriers, it is the responsibility of all stakeholders to help adolescents to adopt healthy lifestyle in all aspects to have a healthier nation. A self-reported anthropometric measurement in adolescents can be used to reach out to the target population.
Keywords: prevalence; adolescents; obesity; overweight; urban